A Cytotoxic Activity of Ethanol Extract of Yellow Root Stem (Arcangelisia flava (L.) Merr.) and Its Effect on Expression of Bcl-2 and Bcl-xL Genes in MCF-7 Cells - Safitri, Devita; Frihani, Assyifa Adelia; Nisa, Sabila Alfa; Kresnadipayana, Dian; Herdwiani, Wiwin (Biomedika, 2022)
Breast cancer was the main cause of death in women on the world, the percentage of breast cancer deaths in Indonesia reaching 9.6% with a prevalence of 201,143 cases of total cancer cases in 2020. The increasing incidence of breast cancer caused the use of breast cancer drugs to increase, especially natural ingredients that could be used as an alternative treatment for breast cancer with minimal side effects. Yellow root (Arcangelisia flava (L.) Merr.) contained berberine compounds which was known to have cytotoxic activity. he aim of this study was to determine the cytotoxic activity of the yellow root stem extract (Arcangelisia flava (L.) Merr.) and its effect on the expression of Bcl-2 and Bcl-xL in MCF-7 breast cancer cells. Extraction was obtained by maceration method with 70% ethanol as solvent. The method of testing cytotoxic activity using the MTT method assay at the concentration series (2800; 1400; 700; 350; 175; 87.5; 43.75) μg/ml then calculated the IC50 value using linear regression. The narrative review was conducted by collecting data from various online research journals using the keywords cytotoxicity of extracts of yellow root (Arcangelisia flava (L.) Merr.) AND the effect on the expression of Bcl-2 and Bcl-xL genes in MCF-7 cells. The results of the cytotoxic test showed that the extract had cytotoxic activity against MCF-7 breast cancer cells with an IC50 of 838.67 μg/ml so that the cytotoxic effect was moderate (100-1000 μg/ml) and the results of the study of the effect of protein expression on cancer cells showed that berberine contained in yellow root can reduce the expression of Bcl-2 and Bcl-xL through the mitochondrial intrinsic pathway in MCF-7 breast cancer cells so that it can induce apoptosis induction.